Silicon Photonics Chip for Inter-modal Four Wave Mixing on a Broad Wavelength Range - Signorini, Stefano; Finazzer, Matteo; Bernard, Martino; Ghulinyan, Mher; Pucker, Georg; Pavesi, Lorenzo (Frontiers in Physics, 2019)
We design, fabricate and test an integrated silicon photonics chip for inter-modal four wave mixing, whose phase-matching relays on the modal dispersions of different waveguide modes. This phase-matching technique allows for tunable and broadband wavelength conversion and generation. We demonstrate that idler and signal photons can be generated with 800 nm spectral distance in between. We measure several inter-modal combinations, with up to the third order mode involvement. We demonstrate a maximum conversion efficiency of -12.4 dB from 1468.5 nm to 1641.1 nm with a bandwidth of 11 nm. We also prove the high and broadband tunability of the generated signal by scanning the pump wavelength when the signal wavelength is fixed. All these features make the inter-modal four wave mixing a viable solution for all optical processing in the near as well as in the mid infrared and for quantum applications.